Antioxidant Enzymes, Antioxidant Vitamins,Glutathione And Uric Acid Levels In Nasal Polyp(S) - SHEETAL D,; SREEKANTHA,; YOGESH B,; AMARNATH M,; MANJUNATH P,; KODLIWADMATHM.V,; SREENIVAS RAO.K,; HARISH BHAT,; VISHAL KALASKAR, (International Journal of Pharma and Bio Sciences, 2012)
Nasal polyp (NP) is an inflammatory pedunculated part of nasal mucosa. It is the most common disease causing the nasal obstruction and sinusitis. Role of free radicals has been proposed in the etiopathogenesis of many diseases including nasal polyp(s).Reactive oxygen species (ROS) produce oxidative stress (OS) resulting in lipid and protein oxidation. The amount of free radical injury or oxidative stress is assessed by altered levels of antioxidants. So, we have estimated superoxide dismutase (SOD), catalase (CAT) as antioxidant enzymes, ascorbic acid (Vit C) and tocopherol (Vit E) as antioxidant vitamins and glutathione (GSH) and uric acid as antioxidants in 27 patients each in bronchial asthma nasal polyp group (BANP group) and allergy nasal polyp group (ANP group) with 30 normal healthy age matched controls by spectrophotometric method and uricacid in chemistry autoanalyser P-800. Significantly decreased levels (p<0.001) of SOD, CAT, Vit C, Vit E, GSH and significantly increased levels (p<0.001) of uric acid were found in both BANP group and ANP group when compared to controls. Levels of all antioxidant parameters were altered more in BANP group compared to ANP group. The documented results may be due to their utilization during scavenging of ROS in disease process. Adequate supplementation of related antioxidants may limit and prevent the disease process in both the groups.